Workshop Pentingnya Product Branding Dalam Penjualan di Ekosistem Digital - Yanuar Rahmadan; Sheila Silvia Permatasari; Kiko Armenita Julito; Endyastuti Pravitasari (Jurnal Pemberdayaan Nusantara, 2023)
The main purpose of the community outreach program at Dinas Koperasi dan UMKM Garut is to improve the knowledge and awareness from the MSMEs in Garut regrading the importance of integrating their sales to the digital ecosystem. The community outreach program used workshop method and devided the program into three different sessions. The workshop was carried out by lecturers from Universitas 17 August 1945 Jakarta. The workshop was specifically intended for the MSMEs as they need to keep adapted in today’s uncertain economic condition post Covid-19 pandemic. One of the findings is that there is a negative perception among the MSMEs in Garut on the brand from Indonesia. The workshop aimed not only to improve the Nation Brand Index of Indonesia but also to improve knowledges on the importance of brand awareness and E-WOM optimalization.